Scarlet eaudiobook - Lawhead, Stephen R. (King Raven Trilogy., 2007)
After losing everything he owns, forester Will Scarlet embarks on a search for none other than King Raven, whose exploits have already become legendary. After fulfilling his quest--and proving himself a skilled and loyal companion--Will joins the heroic archer and his men. Now, however, Will is in prison for a crime he did not commit. His sentence is death by hanging--unless he delivers King Raven and his band of cohorts. That, of course, he will never do. Scarlet continues Stephen R. Lawhead's riveting saga that began with the novel Hood , which relocated the legend of Robin Hood to the Welsh countryside and its dark forests. Lawhead's trilogy conjures up an ancient past and holds a mirror to contemporary realities.